HUBUNGAN PERILAKU MEROKOK DENGAN KOMPLIKASI PADA PASIEN DM TIPE 2 - Wiwik " Ardila; Yesi " Hasneli; Oswati " Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research was to identity the relationship between smoking behavior with complications in patients with type two diabetes mellitus. The research used correlation descriptive method with cross sectional design. In this research used 54 respondents with accidental sampling which were recruited based on inclusion and exclusion criteria. The instrument in this research was a smoking behavior questionnaire and the complications in patients with type two diabetes mellitus observation sheet. The analyzed used univariate and bivariate with Kolmogorov Smirnov Z test. The result showed that there is a relationship between smoking behavior with diabetes mellitus complications to patiens type two with p value of 0,008, where p value < α (p value < 0,05). It is recommended for patients to improve the self-awareness of a healthy lifestyle and knowledge of health education to prevent occurred diabetes mellitus complications, both macrovascular and microvascular. Keyword: complications, diabetes mellitus, smoking behavior